Recombinant Human Brain Natriuretic Peptide Attenuates Myocardial Ischemia-Reperfusion Injury by Inhibiting CD4+ T Cell Proliferation via PI3K/AKT/mTOR Pathway Activation - Kun-Peng Li; Hai-Yan Zhang; Xiao-Dong Xu; Ming-Yang; Tie-Jun Li; Shu-Tian Song (Cardiovascular Therapeutics)
Inflammation plays a major role in the development of myocardial ischemia-reperfusion (IR) injury. Recombinant human brain natriuretic peptide (rhBNP), a man-made version of a peptide that is elevated in heart failure, exhibits anti-inflammatory effects in various tissues. However, its role in myocardial IR injury remains unclear. In this study, we demonstrate that treatment with rhBNP provided protection for mice against myocardial IR injury as manifested by reduced infarct size and well-preserved myocardial, attenuated inflammatory infiltration and CD4+ T cell proliferation function, and inhibited expression of proinflammatory related genes. Furthermore, mechanistic studies revealed that rhBNP inhibited Jurkat T proliferation by promoting PI3K/AKT/mTOR phosphorylation. Collectively, our data suggest that the administration of rhBNP during IR injury could expand our understanding of the cardioprotective effects of rhBNP.